2020
DOI: 10.1155/2020/5741387
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Development and Its Spatial Spillover Effect on Green Total Factor Productivity: Evidence from 30 Provinces in China

Abstract: The relationship between financial development and green economic growth has received much attention in recent years. Research on the relationship between financial development and green total factor productivity (GTFP) is of great importance to China and other countries. This study has attempted to reveal the spatial distribution of China’s provincial GTFP and impact of financial development on GTFP by using the method of GML index based on SBM-DDF and the spatial Durbin model (SDM) during the period 1996–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 47 publications
0
32
0
Order By: Relevance
“…In the mechanism analysis, we can see that the adjustment effect of the innovation input level and infrastructure investment level on the land market is heterogeneous [61]. On the one hand, with the continuous development of the land market, the financial revenue of the local government is also increasing year by year, which is leading to the continuous increase in scientific research investment and innovation investment, and the number of patents is also growing rapidly.…”
Section: Discussion Empirical Analysis and Discussionmentioning
confidence: 99%
“…In the mechanism analysis, we can see that the adjustment effect of the innovation input level and infrastructure investment level on the land market is heterogeneous [61]. On the one hand, with the continuous development of the land market, the financial revenue of the local government is also increasing year by year, which is leading to the continuous increase in scientific research investment and innovation investment, and the number of patents is also growing rapidly.…”
Section: Discussion Empirical Analysis and Discussionmentioning
confidence: 99%
“…From the perspective of industrial ecological chain, technological innovation promotes the upgrading of the regional structure and the exchange and cooperation between the industrial structure, and innovation jointly promotes technological innovation and industrial structure upgrading (Greunz, 2004;Motohashi and Yun, 2007;Altenburg et al, 2008), and adjusting industrial structure can improve energy utilization efficiency as well (Zhao et al, 2010;Zhou et al, 2013;Yu et al, 2016;Wang et al, 2020). The technical level of energy TFP production depends on the technological innovation ability; empirical results show that the enhancement of technological innovation ability can effectively improve energy efficiency and reduce energy consumption intensity (Du and Yan, 2009;Zhong and Li, 2020). Wagner et al (2014) found from innovative activities, with potential environmental impact that the potential of technological innovation is unlimited.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, 158 countries with complete data are selected as the initial research samples. First, when measuring the explanatory variable dynamic energy TFP, a DEA model with a global reference set is used, so a full sample base must be built (Li et al, 2019;Li and Liao, 2020;Zhong and Li, 2020). Data of the input-output indicators are derived from PWT 10.0 (Feenstra et al, 2015), US Energy Information (EIA), and World Bank Database, containing 5,875 samples from 158 countries or regions for 1980-2018.…”
Section: Data Sourcesmentioning
confidence: 99%